Local covariant region detection based on image contour corner - Xu, Ling. (2013)
In this paper, a local covariant region detection algorithm is proposed based on image contour corners. We define the corner response function as the DoB (Difference of B-spline) norm of the evolution difference of the image contour. A new feature region detection algorithm is designed combining corner points from the DoB algorithm and the scale invariance of the contour direction in the corner neighborhood. Finally, the feature covariant regions in multiple groups of interfered image are matched using the repetition rate criterion. The experimental results illustrate that the proposed algorithm has the properties such as simple calculation, easy realization and better robustness.